2020
DOI: 10.1016/j.isci.2020.101498
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Enabled Laser 3D Printing of High-Performance Titanium with Highly Concentrated Reinforcement

Abstract: Summary Zero- to two-dimensional nanomaterials have been incorporated into metal-matrices to improve the strength of metals, but challengingly, high-volume-fraction nanomaterials are difficult to disperse uniformly in metal matrices, severely degrading the ductility of conventionally processed metals. Here, a considerably dense uniform dispersion of in situ formed nanoscale lamellar TiC reinforcement (16.1 wt %) in Ti matrix is achieved through laser-tailored 3D printing and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 58 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…Postetching analysis in the SEM reveals what appear to be carbide formations on the surface, which are not observed in the control Ti64 samples. Their small scale (%500 nm) prevented their direct identification by EDS analysis, but the visual observation aligns with those of Gu et al [13] Figure 7 shows a progression of this carbide formation as observed in SEM. In Figure 7a an intact CNT is observed moving in and out of plane of the observable surface-identified by its dimensions and charging of electrons.…”
Section: Effects On Microstructuresupporting
confidence: 86%
See 3 more Smart Citations
“…Postetching analysis in the SEM reveals what appear to be carbide formations on the surface, which are not observed in the control Ti64 samples. Their small scale (%500 nm) prevented their direct identification by EDS analysis, but the visual observation aligns with those of Gu et al [13] Figure 7 shows a progression of this carbide formation as observed in SEM. In Figure 7a an intact CNT is observed moving in and out of plane of the observable surface-identified by its dimensions and charging of electrons.…”
Section: Effects On Microstructuresupporting
confidence: 86%
“…In Figure 7a an intact CNT is observed moving in and out of plane of the observable surface-identified by its dimensions and charging of electrons. It is noteworthy that this appears to be the first study on the SLM of Ti-CNT where some CNTs survive into the final printed structure; this is attributed to the lower laser energy density used as compared to previous studies [13,14,29] and the relatively high purity (>95 wt%) of CNTs used in the current study. Figure 7b then shows a linear chain of carbides with similar morphology to the nanotubes used in this study, representing a CNT that has entirely reacted to TiC x .…”
Section: Effects On Microstructurementioning
confidence: 80%
See 2 more Smart Citations
“…It has been shown that it is possible to etch silicon nanotubes with very specific dimensions using oxygen plasma etching 33 . Moreover, Chen et al were able to fabricate mutipodal Silicon Nanotubes via Anodic Aluminum Oxide template-assisted Approach 34 . Not to mention that with the use of additive manufacturing and with the presence of rapidly growing technologies like nano-scale 3D printing 35 , the fabrication of BPCs seems very feasible.…”
Section: Resultsmentioning
confidence: 99%